PEMBUATAN PUPUK ORGANIK DARI SAMPAH MASYARAKAT - Allwar Allwar (UII, 2013)
Trash can bring disastrous consequences for public health if they are notinsurmountable. If the waste is disposed or stacked haphazardly without propermanagement, it will cause a variety of health problems that occur in the community.Some of us did not realize that every day buildup of waste both organic garbage(wastethat can be described) or inorganic (waste that can not be described). On the Krajan,every morning most of the mothers clean up his yard from the dried leaves are falling.But the women in Krajan have not been able to manage the waste becomes moreuseful.That is not why I entered this program, to provide new knowledge to the mothers thatactually dry leaf litter can be used as fertilizer. The program is carried out because theystill lack awareness of mothers about the dangers of burning trash for environmentalsustainability, so that people are not maintaining the environment in the surroundingarea. The objective of this program is to broaden the mothers to be able to processwaste into more useful items, namely fertilizers, and is also expected by theimplementation of this program, citizens become better maintain the environmentaround it. The event begins with an introduction to the program, the provision ofmaterial about what is organic waste, organic fertilizer third practice. The resultsobtained are people Krajan can tell which are organic and inorganic waste. For themothers, of the waste can be made into fertilizer, so Krajan so much cleaner.